Feminine hygiene kit for homeless / Nor Suhaiza Md Khalid … [et al.] - Md Khalid, Nor Suhaiza; Kamarunzaman, Nur Zafifa; Abdullah, Aida; Ayob, Nor Azira; Lokman, Asmidar (Division of Research and Industry Linkages, 2017)
Homelessness is an emerging social issue especially in the city areas. This issue has become rampant with the uncertain global economic conditions alongside with poor coping mechanisms among the individuals. Homelessness requires the necessity of life to be fulfilled, including physical and psychological needs. There are efforts to provide temporary shelters for them, but were not targeted throughout the country. Furthermore, women who lost their dependent face a three-fold risk to become homeless compared to women with dependent. Therefore, various efforts are made to mitigate the effect of homeless women particularly in the cities. Hygiene is one of the salient points targeted in helping these women. It is vital to acknowledge that male and female have different needs in hygiene care. Therefore, the objective of this innovation is to introduce 'Feminine Hygiene Kit’ that caters the homeless women needs. The kit consists of basic hygiene care for women such as sanitary pad, disposable panties, nail clipper, shaver, soap and shampoo, toothbrush and toothpaste, cotton bud and small towel. With this innovation, homeless women are given the basic right to health as well as deterring themselves from any disease that cause from unhygienic self-care, simultaneously their physical and psychological well-being emphasised. This kit is unique because it focuses on feminine hygiene care with a minimum cost, handy and for daily use. It is estimated to last for a week consumption.